Screening of electrospray operating parameters in the production of alginate-royal jelly microbeads using factorial design - Mohd Rus, Shaiqah; Abu Yazid, Anis Afiful Huda; Mohamad, Izzuddin; Noor Ismadi, Muhammad Nur Shafiq; Mohd Azlan, Nur Hakimah; Rahman, Siti Radziah; Doolaanea, Abd Almonem; Adina, Anugerah Budipratama; Haris @ Harith, Muhammad Salahuddin (Wolters Kluwer Health, 2019)
Introduction: Royal jelly (RJ) has been consumed as food or as a supplement because of its high nutritional and medicinal values. A fresh harvested RJ is yellowish to whitish in colour and contains proteins, free amino acids, lipids, vitamins, and sugar. Without proper storage conditions such as at 4 °C, RJ’s colour changes to much darker yellow and produces a rancid smell. In order to prolong its shelf life, RJ is usually mixed with honey. Alginate, a natural and edible polymer derived from seaweed is commonly used to encapsulate drugs and food due to its ability to form gels by reacting with divalent cations. However, there is a lack of research on the microencapsulation of RJ in alginate using electrospray. The electrospray technique has the advantage in producing consistent size and shape of alginate microbeads under optimum parameters. Objectives: This research aims to optimize electrospray operating parameters in producing alginate-royal jelly microbeads. Methods: Optimization of alginate-royal jelly microbeads electrospray parameters was done using 24 factorial design with 3 centre points (19 runs). The studied parameters were flow rate, high voltage, nozzle size, and tip-to-collector distance while the responses were particle size, particle size distribution, and sphericity factor. The responses of each run were analysed using Design Expert® software. Results: Nozzle size is a significant parameter that influences the particle size. Flow rate is a significant parameter influencing the sphericity factor. Conclusion: Screening of the electrospray operating parameters paves the way in determining the significant parameters and their design space to produce consistent alginate-RJ microbeads.